PENGARUH RASIO PROFITABILITAS DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Sektor industri barang konsumsi Yang Terdaftar Di Bursa Efek Indonesia 2016-2019) - Rizal Amri; Abdul Wahid Mahsuni; M. Cholid Mahsuni (Universitas Islam Malang, 2021)
This study was conducted to analyze the ratio of profitability and solvency to firm value. Case study of manufacturing companies in the consumer goods industry sub-sector listed on the Indonesia Stock Exchange in 2016-2019. The sample used in this study is a manufacturing company in the Consumer Goods Industry sub-sector which is listed on the Indonesia Stock Exchange (IDX) for the period 2016 – 2019. Based on the test results in the previous chapter, the partial test results show that profitability has an effect on firm value in the company. Manufacturing sub-sector of the Consumer Goods Industry Listed on the Indonesia Stock Exchange 2016-2019. Partial test results show that solvency has no significant effect on firm value in manufacturing companies in the consumer goods industry sub-sector listed on the Indonesia Stock Exchange in 2016-2019. Simultaneous test results show that profitability and solvency have a significant effect on firm value in manufacturing companies in the consumer goods industry sub-sector listed on the Indonesia Stock Exchange in 2016-2019.Keywords: Profitability, Solvency, Firm Value